Penerapan Total Quality Management Terhadap Dampak Kinerja Manajerial dan Laba Perusahaan pada UMKM Yogyakarta - Chaerunisak, Uum Helmina; Aji, Andri Waskita (Universitas Bina Sarana Informatika, 2020)
Abstract - Business competition among UMKM is also getting tougher and requires UMKM to try to maximize their ability to compete with other business. In order to compete, the company is expected to improve quality in terms of managerial performance. This study aims to determine the Effect of Total Quality Management on Managerial Performance and Company Profit (Case Study of UMKM in Yogyakarta). The company in applying TQM especially in the improvement of its production will have an effect by increasing the quality of its managerial performance, which is headed by a manager and can increase the profits obtained by the company. There are three variables used in this study, namely Total Quality Management (TQM) (X), Managerial Performance (Y1), and Company Profit (Y2). The sample used was 74 respondents from the population of UMKM in Yogyakarta. The results of this study, TQM has an effect on Managerial Performance with alpha value of 0.000 This proves that the first hypothesis is supported, TQM has no effect on Company Profit with evidenced by the significance level that exceeds the alpha value of 0.305. thus the second hypothesis is not supported. Keywords: Total Quality Management, Managerial Performance, Company Profit